i need help with the following problem. it would be helpful if you can include all the steps to get the answer

g(x)= x^2 + 4

find g(-3), g(0), , g(-1), g(7), g(v), g(x+h), and g(a+h) - g(a) /H

g(x)= x^{2} + 4

g(-3) = (-3)^{2}+4 = 9+4 =13

g(0)= 0^{2}+4 =4

g(-1)= (-1)^{2}+4 =1+4=5

g(7) = 7^{2}+4 = 49+4 =53

g(v)= v^{2}+4

g(x+h)= (x+h)^{2}+4= x^{2}+2hx+h^{2}+4

g(a+h) = (a+h)^{2}+4= a^{2}+2ah+h^{2}+4

g(a-h) = (a-h)^{2}+4= a^{2}-2ah+h^{2}+4

g(a+h)-g(a-h)= 4ah

[g(a+h)-g(a-h)]/h = 4a

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up